COGNITIVE RESTRUCTURING AS A GROUP COUNSELING STRATEGY TO ADDRESS CAREER ANXIETY IN MADRASAH ALIYAH: A NARRATIVE REVIEW - 'Atika, Wilda; Nawawi, Erfan (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
This study narratively examines the effectiveness of Cognitive Restructuring in group counseling as a strategy to reduce career anxiety among Islamic senior high school students. As a core technique within Cognitive Behavioral Therapy (CBT), Cognitive Restructuring focuses on identifying and modifying negative thought patterns into more rational and adaptive cognitions. Using a narrative review design, six empirical studies published between 2019–2024 were analyzed thematically, selected from Google Scholar, DOAJ, and Portal Garuda based on relevance to adolescents and CBT interventions. The findings indicate that Cognitive Restructuring consistently enhances self-confidence, emotional regulation, self-acceptance, and academic resilience, which collectively reduce career anxiety. Theoretically, this study reinforces the importance of cognitive counseling approaches within Islamic education and suggests integrating Islamic spiritual values in counseling practices. Future research should empirically test Cognitive Restructuring’s quantitative impact on career anxiety and readiness among madrasah students.